Estudo dos problemas de corte unidimensional e bidimensional na fabricação de salas seguras para armazenamento de dados - Flamini Filho, Marcio Cezar (Universidade Federal de São Carlos, 2025)
In recent years, the exponential increase in global data generation—driven by online transactions, social networks, and internet-connected devices—has posed significant challenges for the effective management of large volumes of digital information. This scenario has fueled the growth of the secure room construction sector, especially among companies that need to store sensitive data, such as data centers. This study focuses on the production dynamics of modules intended for secure rooms and vaults in a company based in Sorocaba, Brazil. In this context, the adopted production system is project-based, presenting specific challenges, particularly in the precise cutting of sheets and bars. The main objective is to study optimization models for one- and two-dimensional cutting to assess the potential for reducing material waste, with an emphasis on reducing associated costs. Furthermore, the aim is to analyze the feasibility of working with stock parts, which can provide both financial and environmental benefits. To this end, different scenarios were defined to represent possible decision-making alternatives within the company, primarily structured through goal-programming models. The results indicate that both the amount of raw material used and the volume of stored parts vary depending on the scenario adopted, leaving it up to production management to choose the most appropriate alternative according to the company's operational priorities and constraints.
Study of unidimensional and bidimensional cutting problems in secure room fabrication for data storage
Keywords: Problema de Corte de Estoque; Corte Unidimensional; Problema de Corte Bidimensional Guilhotinado; Programação por Metas; Fabricação de Salas Seguras para Data Centers; Cutting Stock Problem; One-Dimensional Cutting; Two-Dimensional Guillotine Cutting Problem; Goal Programming; Secure Room Manufacturing for Data Centers; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL